Anti-Allergic Effects of Quercetin and Quercetin Liposomes in RBL-2H3 Cells - Zhang, Yanhui; Guan, Rongfa; Huang, Haizhi (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background: Quercetin is a kind of flavonoid with important bioactivities, such as hypoglycemic, antioxidant, anti-inflammatory, and anti-allergic properties. Although it is unstable, it is worth exploring how to better exert its anti-allergic effect. Objective: The current study aimed to elucidate the anti-allergic effect of quercetin liposomes on RBL-2H3 cells in vitro. Methods: Quercetin liposomes were prepared to improve the anti-allergic activity of quercetin through a green thin-film dispersion method. We compared the anti-allergic effects of quercetin and quercetin liposomes in RBL-2H3 cells. The anti-allergic activity of the quercetin liposomes was evaluated by the level of β-hexosaminidase, histamine, Ca2+, IL-4, IL-8, and MCP-1. Results: The results showed that quercetin liposomes could significantly restrain the release of β-hexosaminidase and histamine, calcium influx, and the expression of inflammatory factors, whose effect is stronger than quercetin. Conclusion: Collectively, our research suggests that the quercetin liposome can be used as a potential allergy antagonist.
Keywords: RBL-2H3 cells